(untitled) (Circe de clásicos y modernos, 2018)
This article portrays the life and personality of Joseph Haydn (1732-1809) and his outstanding contribution to the world of music, both as a court musician at the service of the Esterházy Princes and as a free musician in London and Vienna. His contribution to the development of the sonata and symphony forms and of the string quartet is depicted as well as his work in the genre opera and oratorium. A chapter is also devoted to stressing Haydn’s good character and humorous disposition which he expressed in his music and in his daily life.